An environmental study of the ultraluminous X-ray source population in early-type galaxies - Plotkin, Richard; Gallo, E.; Miller, B.; Baldassare, V.; Treu, T.; Woo, J. (Institute of Physics Publishing, 2014)
Ultraluminous X-ray sources (ULXs) are some of the brightest phenomena found outside of a galaxy's nucleus, and their explanation typically invokes accretion of material onto a black hole. Here, we perform the largest population study to date of ULXs in early-type galaxies, focusing on whether a galaxy's large-scale environment can affect its ULX content. Using the AMUSE survey, which includes homogeneous X-ray coverage of 100 elliptical galaxies in the Virgo cluster and a similar number of elliptical galaxies in the field (spanning stellar masses of 108-1012 M ☉), we identify 37.9 ± 10.1 ULXs in Virgo and 28.1 ± 8.7 ULXs in the field. Across both samples, we constrain the number of ULXs per unit stellar mass, i.e., the ULX specific frequency, to be 0.062 ± 0.013 ULXs per 10 10 M ☉ (or about 1 ULX per 1.6 × 10 11 M ☉ of galaxy stellar mass). We find that the number of ULXs, the specific frequency of ULXs, and the average ULX spectral properties are all similar in both cluster and field environments. Contrary to late-type galaxies, we do not see any trend between specific ULX frequency and host galaxy stellar mass, and we show that dwarf ellipticals host fewer ULXs than later-type dwarf galaxies at a statistically meaningful level. Our results are consistent with ULXs in early-type galaxies probing the luminous tail of the low-mass X-ray binary population, and are briefly discussed in context of the influence of gravitational interactions on the long-term evolution of a galaxy's (older) stellar population.